Stimulasi Kreativitas Anak Melalui Media Loose Part di KB ONSIF Kota Gunungsitoli - Rismawati Munthe (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The first stimulation of creativity in early childhood is so that children can express themselves creatively. Second, they can think creatively as an ability to resolve conflicts or solve problems. Third, independent creative practices give someone pleasure to produce useful goods. Fourth, creativity to improve the standard of living and norms of life. KB ONSIF which is still located in the village office of hamlet I, Onozitoli Sifafo village is a supporting factor for the large number of loose parts materials available, educators change the environmental conditions that are full of drinking bottles, paper and cardboard scattered around the building into educational play media for children. This conversion power can not only be used as a learning medium, but can also create cleanliness in the environment around the school. Loose parts are objects that are easily found in our environment, such as twigs, shells, used plastic packaging, plastic bottles, cardboard, metal, cloth, etc. These materials can be obtained by teachers and parents anywhere without spending money. The purpose of this study was to see the use of loose parts media in stimulating children. The research method used was descriptive qualitative by obtaining data from the results of observations, interviews and documentation. The research results obtained through loose parts media learning activities are able to stimulate children's creativity, as evidenced by the results of children's work based on children's imagination without the help of teachers.